Increase in Purchase Intention through Source Credibility, Recommendation Credibility, and Psychological State: Brand Awareness Mediates - Supriyadi, Ari; Rahmat Syah, Tantri Yanuar (Journal of Business and Management Review, 2024)
Research Aims:  The purpose of this study was built to determine the positive effect of increasing Purchase Intention through Source Credibility, Recommendation Credibility, and Psychological State: Brand Awareness being the mediation Design/methodology/approach:  The purposive sampling method was designed in this study with 389 online customers from several well-known skincare brands in Indonesia. The data was analyzed using the Structural Equation Model (SEM) with SmartPLS 3.0 Research Findings:  The findings of this study being Source Credibility has a positive effect on Recommendation Credibility. Then Recommendation Credibility has a positive effect on Psychological State and Brand Awareness. Furthermore, Recommendation Credibility, Psychological State, and Brand Awareness have a positive effect on Purchase Intention. Brand Awareness manages to be a mediating effect between Recommendation Credibility and Purchase Intention. Managerial implications in this study for researchers and practitioners should not underestimate the importance of social media, establish a cooperative relationship between companies and celebrities for continuity, and know the importance of pre-purchase psychological states Theoretical Contribution/Originality: The study contributes to the existing literature by providing insights into the complex interplay of factors influencing Purchase Intention. It highlights the importance of social media and the role of celebrities in marketing strategies, as well as the significance of pre-purchase psychological states and the mediating effect of Brand Awareness. Keywords:  Source Credibility, Recommendation Credibility, Psychological State, Brand Awareness, Purchase Intention